Jazz Diasporas : Race, Music, and Migration in Post-World War II Paris - Braggs, Rashida K., 1976- (Book collections on Project MUSE., 2016)
"At the close of the Second World War, waves of African American musicians migrated to Paris, eager to thrive in its reinvigorated jazz scene. Jazz Diasporas challenges the notion that Paris was a color-blind paradise for African Americans. On the contrary, musicians--and African American artists based in Europe like writer and social critic James Baldwin--adopted a variety of strategies to cope with the cultural and social assumptions that greeted them throughout their careers in Paris, particularly in light of the cultural struggles over race and identity that gripped France as colonial conflicts like the Algerian War escalated. Through case studies of prominent musicians and thoughtful analysis of personal interviews, music, film, and literature, Rashida K. Braggs investigates the impact of this post-war musical migration. Examining a number of players in the jazz scene, including Sidney Bechet, Inez Cavanaugh, and Kenny Clarke, Braggs identifies how they performed both as musicians and as African Americans. The collaborations that they and other African Americans created with French musicians and critics complicated racial and cultural understandings of who could play and represent "authentic" jazz. Their role in French society challenged their American identity and illusions of France as a racial safe haven. In this post-war era of collapsing nations and empires, African American jazz players and their French counterparts destabilized set notions of identity. Sliding in and out of black and white and American and French identities, they created collaborative spaces for mobile and mobilized musical identities, what Braggs terms 'jazz diasporas.'"--Provided by publisher.